Facilitating Imagine Arts in residential care homes: the artists’ perspectives - Broome, Emma; Dening, Tom; Schneider, Justine M. (Taylor and Francis, 2017)
Background: This study explores factors affecting the successful facilitation of a residential arts programme. The aim was to identify barriers and describe how they could be overcome, this was both formative, to help shape the programme, and summative, to inform best practice and future arts interventions. Methods: An exploratory qualitative design examined the views of the artists administering the arts programme. Results: The data was analysed using thematic analysis. Four main themes were identified; contextual factors, perceiving and responding to needs, facilitating relationships and building confidence. Conclusion: Findings provide insight into practical aspects of facilitating arts programmes in residential care. Some of the identified barriers may have simple solutions which can easily be incorporated into everyday best practice. This research provides a start for understanding the role of artists within care homes and how they aid the implementation and integration of arts programmes into the care of people with dementia.